2018
DOI: 10.1186/s12885-018-4054-x
|View full text |Cite
|
Sign up to set email alerts
|

It is no longer the time to disregard thyroid metastases from breast cancer: a case report and review of the literature

Abstract: BackgroundMetastases to the thyroid gland are more frequent than previously thought, although most of them are occult or not clinically relevant. Overall, only 42 cases of metastases to thyroid from breast cancer have been reported thus far. Here we report the case of a patient with breast cancer metastatic to the thyroid. We also review the 42 previously reported cases (published between 1962 and 2012). This is the first review about metastases to thyroid gland from breast cancer.Case presentationA 64-year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 23 publications
2
21
0
8
Order By: Relevance
“…Some studies reported that patients with thyroid metastases from breast cancer were symptomless and presented malignant thyroid nodules by ultrasound [1,3]. Similar clinical manifestations were reported by Owens et al [11] and Pensabene et al [4]. In our case, the patient also presented no symptoms related to the thyroid disease.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Some studies reported that patients with thyroid metastases from breast cancer were symptomless and presented malignant thyroid nodules by ultrasound [1,3]. Similar clinical manifestations were reported by Owens et al [11] and Pensabene et al [4]. In our case, the patient also presented no symptoms related to the thyroid disease.…”
Section: Discussionsupporting
confidence: 88%
“…In addition,the US features of thyroid metastases from breast cancer are not speci c. Zhou et al [1] reported that six patients showed heterogeneous echogenicity with scattered microcalci cation, and two patients had hypoechoic solid nodule on US. Pensabene et al [4] reported that one case showed enlarged thyroid with thyroid nodules on US. Similar thyroid nodule on US was reported by Magers et al [6], Lacka et al [7] and Owens et al [11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations